System architectures for just-in-time video transcoding mode decision on heterogeneous high performance computers : doctoral thesis - Dragić, Leon (L. Dragić ; Fakultet elektrotehnike i računarstva, 2019)
Today, Internet traffic is dominated by video content and projections show that this trend will continue to increase. The performance growth of the technology also allowed the introduction of High Definition (HD) and Ultra-High Definition (UHD) videos. These are some of the facts that point out that efficiency in storing and streaming video content is a necessity. Current methods and paradigms for storing and streaming multimedia are not sustainable. To provide optimal efficiency of storing and streaming video, it is necessary to have the possibility to encode the video with occasion-specific parameters. This can be achieved using just-in-time transcoding. Efficient video transcoding requires significant work on modeling, mapping and optimizing parts of the algorithms to different underlying architectural elements. Software optimizations are required but not sufficient, and the use of the hardware accelerator kernels for critical parts of the algorithm is mandatory to enable efficient processing from the performance, power and QoE perspective. Balancing between these three characteristics in real-time presents a great challenge and is often considered as a critical point called mode decision. Mode decision algorithms can be efficiently co-designed with hardware-based accelerator kernels to provide greater performance, while maintaining the quality and compression efficiency.In this thesis, two original scientific contributions were achieved:1. Design of performance-optimized just-in-time video transcoding mode decision algorithms and hardware-based accelerator kernels for heterogeneous high performance computers 2. Performance-efficient integration of system architectures composed of implemented just-in-time video transcoding mode decision algorithms and hardware-based accelerator kernels on heterogeneous high performance computers. Keywords: video transcoding, mode decision, just-in-time, HEVC, hw/sw co-design, video encoding, accelerator cores.